Caring for HIV Person in Dermatology - Jibriel, Diaz Azhalea; Dharma, Yoga Prawira Wedha Swara; Nuriasti, Rovera; Pambudi, Balqis Prudena Kurnia; Sugiono, Muhammad Rafly Adrian; Febriana, Nanggi Qoriatul; Dwiandika, Rizki Ary; Zulkifli, Yasmin Sabrina; Larasati, A. A. A. Regina; Senna, Cantika Brilliant; Tahriani, Ridha; Arif Zuhan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
More than 90% of individuals infected with Human Immunodeficiency Virus (HIV) exhibit skin abnormalities that can serve as important clues for early diagnosis, monitoring disease progression, and assessing the effectiveness of antiretroviral therapy (ART). However, the diverse presentation of skin problems often complicates clinical management. Methods: This article is based on a literature review of various international and national publications on skin manifestations in HIV patients, as well as dermatological management guidelines. The analysis focused on the types of skin infections, non-infectious conditions, side effects of ART, and recommended treatment strategies. Results: The literature review revealed that skin problems in HIV patients include fungal infections (such as candidiasis, dermatophytosis), bacterial (CA-MRSA, syphilis), viral (HSV, VZV, HPV, molluscum contagiosum), and non-infectious conditions such as seborrheic dermatitis, psoriasis, and severe drug reactions. These skin conditions are influenced by a weakened immune system, treatment side effects, and socioeconomic factors. Treatment requires a combination of ART therapy, dermatological care tailored to the type of skin problem, and psychosocial support. Conclusion: Skin manifestations in HIV patients reflect their immune system and quality of life. Comprehensive treatment, including ART, dermatological therapy, and a psychosocial approach, has been shown to be effective in reducing morbidity and stigma. The results of this study underscore the importance of interdisciplinary collaboration to improve treatment outcomes for HIV patients with skin problems in Indonesia.